The role of vocabulary learning strategies and vocabulary size on english reading comprehension among Jordanian EFL undergraduates - Aloqaily, Ayham Ahmad (2022)
The current study investigated the relationship among vocabulary learning strategies, vocabulary size towards reading comprehension of Jordanian undergraduate EFL students. In addition, the study tried to find the contribution of vocabulary learning strategies and vocabulary size to reading comprehension of the students. Jordan University of Science and Technology (JUST) was selected according to purposive sampling technique. Data were collected from all 362 undergraduate EFL students randomly selected. The data were collected through a vocabulary learning strategy questionnaire adapted from Bennett (2006). A vocabulary size test developed by Nation (2007) and a TOEFL reading comprehension test were also used in the study. The descriptive statistics showed that Jordanian undergraduate EFL learners were medium strategy users. And the most and least frequently used were belong to social and determination strategies respectively. All different categories of IV vocabulary learning strategies were reported to be used at high and medium level. The students were found to have a vocabulary size of 6200 words. Then, Pearson Product Moment Correlation was conducted to find the relationships between variables. The result showed that three strategies out from five were found to have a positive correlation to reading comprehension, in addition VS was also found to have a positive correlation with reading comprehension. Further the stepwise analysis revealed that only memory strategies and vocabulary size were found to have a contribution to reading comprehension of JUST students.